Serum SUR1 and TRPM4 in patients with subarachnoid hemorrhage. - Uysal, O; DÜNDAR, TOLGA TURAN; Yurtsever, I; Abdallah, A; YURTSEVER, İSMAİL; Dundar, TT; GÜLER, ERAY METİN; Guler, Eray Metin; ÖZER, ÖMER FARUK; Ozer, OF; UYSAL, ÖMER (My University, 2019)
Neuroinflammation plays an important role in neuronal injury after aneurysmal subarachnoid hemorrhage (aSAH). Sulfonylurea receptor 1 (SUR1) and transient receptor potential cation channel subfamily M member 4 (TRPM4) receptors play an important role in the pathogenesis of several neural injuries, such as neural edema, spinal cord damage, stroke, and neuronal damage in aSAH. This study aimed to investigate the relationship of serum SUR1 and TRPM4 levels with the neurological status within the first 15 days after aSAH. In this prospective study, blood samples were collected from 44 consecutive patients on the 1st, 4th, and 14th days after aSAH. Serum SUR1 and TRPM4 levels were measured using an enzyme-linked immunosorbent assay kit. Glasgow coma scale and World Federation of Neurosurgical Societies (WFNS) scores upon presentation and Glasgow outcome scale (GOS) score on the 14th day were recorded. Serum SUR1 and TRPM4 levels on the 1st, 4th, and 14th days were significantly higher in patients with aSAH than in normal individuals. This increase in the levels varied among the 1st, 4th, and 14th days. On the first day, a correlation was observed between serum SUR1, but not TRPM4, levels and the WFNS score. Moreover, on the 14th day, an association of serum SUR1 and TRPM4 levels with the GOS score was noted. Serum SUR1 and TRPM4 levels were significantly upregulated in the peripheral blood samples. Further study is warranted to establish the utility of SUR1 and TRPM4 as biomarkers in patients with aSAH.